2015
DOI: 10.1063/1.4907872
|View full text |Cite
|
Sign up to set email alerts
|

Topological insulator: Bi2Se3/polyvinyl alcohol film-assisted multi-wavelength ultrafast erbium-doped fiber laser

Abstract: We experimentally demonstrate a multi-wavelength ultrafast erbium-doped fiber laser incorporating a μm-scale topological insulator: Bi2Se3/Polyvinyl Alcohol film as both an excellent saturable absorber for mode-locking and a high-nonlinear medium to induce a giant third order optical nonlinear effect for mitigating the mode competition of erbium-doped fiber laser and stabilizing the multi-wavelength oscillation. By properly adjusting the pump power and the polarization state, the single-, dual-, triple-, four-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…Thus, properly increasing highly nonlinear effect in the laser cavity is favorable for generating multi-wavelength pulse. In addition, we also verified it in our recent work [14]. Furthermore, Zhao et al reported on the generation of dual-wavelength rectangular pulse in a Yb-doped fiber laser by using a microfiber-based graphene saturable absorber (GSA) [15].…”
Section: Introductionsupporting
confidence: 85%
“…Thus, properly increasing highly nonlinear effect in the laser cavity is favorable for generating multi-wavelength pulse. In addition, we also verified it in our recent work [14]. Furthermore, Zhao et al reported on the generation of dual-wavelength rectangular pulse in a Yb-doped fiber laser by using a microfiber-based graphene saturable absorber (GSA) [15].…”
Section: Introductionsupporting
confidence: 85%
“…Since then, hydrothermal intercalation/exfoliation has been widely used to produce TIs [17,38,112,[148][149][150]. such as PVA were frequently utilized in the preparation of TI-based SAs [89,108,109,137,151]. In 2014, Liu et al obtained 660-fs pulses generated in an Er-doped fiber laser enabled by Bi 2 Se 3 nanosheets [89].…”
Section: Topological Insulatorsmentioning
confidence: 99%
“…TIs have a broad non-linear response and a large modulation depth [23]; however, the mode-locking stability is, to some extent, lower than graphene. Sometimes, the signal-to-noise ratio of the mode-locked fiber lasers based on TIs SAs are <60 dB [89,108,111,137]. In addition, TI-based SAs tend to obtain Q-switched pulses with pulse width in the order of nanoseconds or microseconds [16,109], which is undesirable as it is usually preferred to achieve ultrashort pulses (picoseconds or sub-picoseconds) for applications in optical communications and material processing [89,114].…”
Section: Topological Insulatorsmentioning
confidence: 99%
“…Some experimental results show that both graphene and topological insulators exhibit broadband saturable absorption at 800 nm [15], 1064 nm [16], and 1550 nm [17], and even at terahertz spectral region [18]. Their applications for multiwavelength pulsed-laser generation (Q-switched/mode locking) have been extensively studied [19][20][21][22][23][24][25]. Moreover, graphene has a giant nonlinear refractive index of n 2 ∼ 10 −7 cm 2 · W −1 , almost nine orders of magnitude larger than that of bulk dielectrics [26], and topological insulators also reach 10 −14 m 2 · W −1 [27], which may cause a strong FWM effect and suppress mode competing, thus improve the stability of a multiwavelength laser.…”
Section: Introductionmentioning
confidence: 99%